2020
DOI: 10.2196/17790
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mobile Health Interventions Promoting Physical Activity and Lifestyle Interventions to Reduce Cardiovascular Risk Among Individuals With Metabolic Syndrome: Systematic Review and Meta-Analysis

Abstract: Background Physical activity and lifestyle interventions, such as a healthy diet, have been proven to be effective approaches to manage metabolic syndrome. However, these interventions require great commitment from patients and clinicians owing to their economic costs, time consumption, and lack of immediate results. Objective The aim of this systematic review and meta-analysis was to analyze the effect of mobile-based health interventions for reducing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 45 publications
(47 reference statements)
2
30
0
2
Order By: Relevance
“…On the contrary, studies in this review revealed low effectiveness of mHealth on FBG. These findings concur with a recent metanalysis consisting of nine studies drawn from LMICs and high-income countries that reported a pooled effect size of −0.39; (P<.001) despite the different populations targeted [95]. FBG is known to be affected by numerous factors, that could be attributable to the low effectiveness found in our review [96].…”
Section: Discussionsupporting
confidence: 92%
“…On the contrary, studies in this review revealed low effectiveness of mHealth on FBG. These findings concur with a recent metanalysis consisting of nine studies drawn from LMICs and high-income countries that reported a pooled effect size of −0.39; (P<.001) despite the different populations targeted [95]. FBG is known to be affected by numerous factors, that could be attributable to the low effectiveness found in our review [96].…”
Section: Discussionsupporting
confidence: 92%
“…Online coaching (e.g., video consultations) and eHealth interventions (e.g., online monitoring) are effective strategies to provide specific BCTs [ 16 , 17 , 18 ]. This is particularly important in long-term CLI interventions, which are distinguished by a behavioral change (year 1) and a maintenance phase (year 2).…”
Section: Discussionmentioning
confidence: 99%
“…CLIs are currently mainly delivered in face-to-face sessions without or with limited use of eHealth. This is a pity because eHealth, especially in combination with face-to-face, is promising in long-term interventions to guide clients toward a sustainable healthy lifestyle [ 16 , 17 , 18 ]. eHealth refers to health services and information delivered or enhanced through internet-related technologies [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since technologies play a key role in everyday life, there is a major increase in the development and use of mobile lifestyle interventions. It is expected that the face-to-face management of health disorders will gradually shift to a more technology supported approach, reducing the large burden on health personnel and resources ( 84 ). Successful health technologies are frequently based on well-grounded cognitive behavioral strategies incorporating psychological elements.…”
Section: Innovative Strategiesmentioning
confidence: 99%